PEREMPUAN TANGGUH, AGEN PERUBAHAN: PERAN STRATEGIS DI BPBD JAWA TIMUR - Aulia Midya Priandini; Dwi Setianingsih (Pusat Pengembangan Pendidikan dan Penelitian Indonesia, 2026)
ABSTRACT The issue of gender equality in disaster management institutions remains a challenge, although the role of women is beginning to be recognized in emergency response. This study aims to examine the strategic roles and obstacles faced by female employees at the Regional Disaster Management Agency (BPBD) of East Java Province. Using a descriptive qualitative approach, informants in this study consisted of female employees directly involved in the field as well as staffing officials. Data collection techniques were conducted through in-depth interviews, direct observation, and documentation analysis. The results showed that women are actively involved in all phases of disaster management, starting from the pre-disaster stage, emergency response, to post-disaster recovery. Their contributions include policy formulation, community education, logistics coordination, psychosocial support, and social reconstruction. However, they face challenges such as biological constraints, cultural stereotypes that underestimate women's capacity, and the double burden of work and domestic responsibilities. Nevertheless, female employees in BPBD Jatim demonstrate resilience and leadership capacity, and are able to become agents of change in the work environment and community. Their involvement increases the inclusiveness and effectiveness of disaster programs, especially in reaching vulnerable groups such as children, the elderly, and pregnant women. This research emphasizes the importance of gender mainstreaming in disaster governance as well as the need for institutional support through gender-sensitive policies and equitable division of tasks. ABSTRAK Isu kesetaraan gender dalam kelembagaan penanggulangan bencana masih menjadi tantangan, meskipun peran perempuan mulai diakui dalam respons darurat. Penelitian ini bertujuan untuk mengkaji peran strategis serta hambatan yang dihadapi oleh pegawai perempuan di Badan Penanggulabngan Bencana Daerah (BPBD) Provinsi Jawa Timur. Dengan pendekatan kualitatif deskriptif, informan dalam penelitian ini terdiri ats pegawai perempuan yang terlibat langsung di lapangan serta pejabat kepegawaian. Teknik pengumpulan data dilakukan melalui wawancara mendalam, observasi langsung, dan analisis dokumentasi. Hasil penelitian menunjukkan bahwa perempuan dilibatkan secara aktif dalam seluruh fase penanggulangan bencana, mulai dari tahap prabencana, tanggap darurat, hingga pemulihan pasca bencana. Kontribusi mereka mencakup perumusan kebijakan, edukasi masyarakat, koordinasi logistik, dukungan psikososial, serta rekonstruksi sosial. Namun, terdapat berbagai tantangan yang mereka hadapi, seperti kendala biologis, stereotip budaya yang meremehkan kapasitas perempuan, serta beban ganda antara pekerjaan dan tanggung jawab domestik. Mesikupn demikian, pegawai perempuan di BPBD Jatim menunjukkan ketangguhan dan kapasitas kepemimpinan, serta mampu menjadi agen perubahan di lingkungan kerja dan masyarakat. Keterlibatan mereka meningkatkan inklusivitas dan efektivitas program kebencanaan, khususnya dalam menjangkau kelompok rentan seperti anak-anak, lansia, dan ibu hamil. Penelitian ini menekankan pentingnya pengarustamaan gender dalam tata kelola bencana serta perlunya dukungan kelembagaan melalui kebijakan yang sensitif gender dan pembagian tugas yang adil